Multiuser Detector For CDMA Communication System Using Evolutionary Programming - Lim, Heng Siong (2001)
In this thesis , an investigation is made on the application of evolutionary programming (EP) in the problem of multiuser detection in code-division multiple access (CDMA) communication systems. EP is a powerful and general global optimization algorithm.